2011
DOI: 10.1016/j.jns.2011.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral hyperschematia without spatial neglect after right frontal lesion

Abstract: a b s t r a c t a r t i c l e i n f oThe disorder is described as a size distortion involving the side of space. We report the case of a woman with an ipsilateral hyperschematia without neglect after a right frontal lesion. The patient has exhibited a disproportionate enlargement of the right-hand side of objects and added more left-sided petals to the drawn daisy. This pathologic behavior is independent from spatial neglect and from classic frontal perseverations. Our data support the presence of a spatial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…A similar HS due to a right-sided frontal vascular lesion has been reported by Saj et al (2011), in a right-handed patient with no spatial neglect or hemianopia. As for the seven patients of the study, drawings from memory revealed a disproportionate expansion and addition of details to the object (a flower, an unfolded cube), reflecting an expansion of the spatial medium but, in Saj's patient, ipsilateral to the side of the lesion (Ipsilateral HS).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A similar HS due to a right-sided frontal vascular lesion has been reported by Saj et al (2011), in a right-handed patient with no spatial neglect or hemianopia. As for the seven patients of the study, drawings from memory revealed a disproportionate expansion and addition of details to the object (a flower, an unfolded cube), reflecting an expansion of the spatial medium but, in Saj's patient, ipsilateral to the side of the lesion (Ipsilateral HS).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, it may reflect a preference for symmetry, stemming from basic perceptual mechanisms, that possibly initially arose during prehistory (Hodgson, 2011). A broadly similar pattern of HS, but ipsilateral to a right frontal lesion, was described by Saj et al (2011) in a patient with no evidence of unilateral spatial neglect, and rightward ipsilesional expansion of drawings both from memory and by copy, with rightward perseveration, when drawing from memory: more petals of a flower on the right-hand side of the drawing; drawing of more sides of an unfolded cube on the right, actually resulting in an incorrect number of faces in the “exploded” cube (one more than required on the right, and possibly another half, left uncompleted). Other clinical reports of distortions of extra-personal and personal spaces, characterized by an underestimation (“hyposchematia”), rather than by an overestimation (“hyperschematia”) are on record.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…He classified the patients as cases of hyper - or hyposchematia , that is patients with the illusory over- or underestimation of the size of the whole body (or of parts of it). The phenomenon has recently been observed in right-brain-damaged patients, both with spatial neglect [37], [38] and without neglect [39].…”
Section: Discussionmentioning
confidence: 87%
“…- a phenomenon that has been described here with caution for the first time in the literature - could be called a “hyperschematia of space.” So far the hyperschematia phenomenon has been described as an enlargement of a portion of an object [37], drawing [38], [39] or body without disorders of size perception (object and drawing) [40]. The concept of hyperschematia was originally proposed by the French otolaryngologist Pierre Bonnier in 1905, based on his clinical observations of patients with vestibular disorders (see [41], [42]).…”
Section: Discussionmentioning
confidence: 99%